Productivity, biochemical composition and toxicity of mixed microalgae in different outdoor cultivation systems - Osman, Norhafizah (2018)
Cultivated microalgae are considered as one of the largest unexploited global biomass resources for a sustainable production of food and replacement of fossil resources. Microalgae may offer a viable alternative to fossil fuels; but, this technology must overcome a number of hurdles before it can compete in the market and be widely deployed. These challenges include strain selection and improvement, nutrients sources, the production of microalgae in large-scale and to improve the economics of the entire system. Though there is much excitement about the potential of microalgae there are abundant of work still required in the field. The potential of microalgae to solve variety of world’s problems was not realized because of bottleneck in microalgal supplies at reasonable cost. Therefore, the objectives of this study are to culture mixed microalgae in different weather conditions; to compare the productivity, proximate compositions, fatty acid profiles and finally the toxicity values of mixed microalgae. The study was conducted in Tapak Ternakan Ikan, Taman Pertanian Universiti and Department of Biology, Faculty of Science, Universiti Putra Malaysia. The temperature and light intensity during the cultivation period were recorded and scored every day. Optical density and dry weight were measured every two days for 10 days. The growth parameters were affected significantly with the differences in weather conditions. The growth parameters showed highest values during hot weather followed by mix and rainy weather conditions. The highest productivity was found during mix weather condition in unsheltered fertilized mesocosm (0.153 ± 0.001 g L-1 day-1). Mixed microalgae also being investigated for their proximate compositions (protein, carbohydrate, and lipid). ANOVA showed that there were significant differences (p< 0.05) observed on the proximate compositions of mixed microalgae grown in different weather and culture conditions. The protein content ranged from 22.72 ± 0.33% to 35.20 ± 0.42% with the highest value obtained from unsheltered fertilized mesocosm during hot weather condition. The carbohydrates were found to be the major constituent of mixed microalgae in this study. The percentage of carbohydrate ranged from 30.57 ± 0.26 to 41.38 ± 0.33% and the highest percentage was from sheltered tilapia mesocosm during rainy weather condition. The highest lipids percentage obtained was 11.28 ± 0.30% which was in sheltered tilapia mesocosm in hot weather condition. For fatty acid compositions, mixed microalgae were extracted for their lipids with methanol: chloroform mixture and after transesterification, the fatty acid methyl ester were analyzed using gas chromatography. Results showed that saturated was the major constituent fatty acids. The average percentages of saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids obtained were 45.62 ± 1.37%, 20.05 ± 1.14%, and 34.33 ± 3.17% respectively. The most dominant fatty acid profiles were C18:3n3 (α-linolenic acid) and C16:0 (palmitic acid), with the overall percentages of 19.97% and 19.40% respectively. The methanolic extracts of mixed microalgae were studied for their toxicity with brine shrimp lethality assays. The LC50 from six samples calculated ranged from 403.98 ppm to 595.79 ppm. The extracts of mixed microalgae exhibited cytotoxic activity against the brine shrimp and considered as containing active or potent components because their LC50 values were less than 1000 ppm. Fertilized sheltered mesocosm has the potential for mixed microalgal production system, the mixed microalgae productivity, proximate composition and lipid acid profile is equivalent or better than terrestrial crops or other expensive single species microalgae production system. The toxicity test also revealed that mixed microalgae can be safely used as feed enhancement for animals.